Ta-W-O nanostructured photoanodes for enhanced solar fuel production: experimental and density functional theory investigation - Nashed, Ramy (AUC Knowledge Fountain, 2014)
The demand on energy is now increasing at an unprecedented rate due to the high technology revolution. Unfortunately, we can no longer depend on the current energy resources, which is mainly fossil fuels, since they are limited and have dangerous impacts on the environment. Hydrogen has recently received a great attention as an alternative fuel because it is a renewable, clean fuel and its energy content is three times that of gasoline. Photoelectrochemical water splitting is a very attractive method of producing hydrogen due to its simplicity and low cost. However, the semiconductor material used as the photoanode still needs to be optimized. Ta2O5 is considered a very promising semiconductor material for water photolysis as its conduction band minimum and valence band maximum are suitable for water splitting beside being highly stable in aqueous solutions. Unfortunately, the material’s bandgap is ~3.9 eV, which limits its absorption spectrum to the ultraviolet region. However, mixing Ta2O5 with WO3 (2.7 eV) is expected to red shifts its absorption to the visible region. We used Density Functional Theory (DFT) to study the electronic and optical properties of Ta-W-O system. Unfortunately, the reported calculations so far failed to estimate the bandgap with an acceptable accuracy that enables the understanding of the optoelectronic properties of the material. Herein, we proposed a new crystal structure and showed that the use of PBE0 hybrid functional reduced the error in bandgap estimation from 95% to 5% resulting in a calculated bandgap of 3.7 eV. This bridges the gap further between ab-initio DFT calculations and experiments. Using the proposed structure for Ta2O5, we calculated the band structure and the hole effective mass for Ta-W-O system. The bandgap calculations showed a large and composition-dependent bowing parameter. The electron excitation from the Ta2O5 valence band to WO3 conduction band at high W content may contribute to the pronounced decrease in the conduction band energy. The staggered bandgap type between Ta2O5 and WO3, as revealed from the energy band diagram, resulted in efficient charge carriers separation. The minimum effective mass occurs along the y-direction and decrease monotonically with increasing W content. Based on the DFT calculations, preliminary experimental work was carried out on low concentration W alloys, namely 2.5% and 10%W. Diffuse reflectance measurements show that the bandgap decreases with increasing W content. This suggests that alloys with high W content are able to harvest a wider range of the solar spectrum and hence higher photo-conversion efficiency. Moreover, XRD analysis showed that the alloys maintained the orthorhombic structure of pristine Ta2O5. However, the lattice parameters expanded as the W content increased owing to larger atomic radius of W. Furthermore, XPS analysis asserts the charge transfer model that was drawn from DFT calculations in which the charge carriers are transferred from the valence band of Ta2O5 to the conduction band of WO3. Finally, the photocurrent of 10%W alloy was increased by about 100x compared to pristine Ta2O5.